An exploration of visual literacy in the English home language and Sepedi home language classroom: a comparative study - Mametja, Reuben (My University, 2023)
The aim of this study is to compare opportunities that teachers of English Home Language (EHL) and Sepedi Home Language (SHL) create to enhance visual literacy skills and to determine the extent to which such opportunities foster the development of critical thinking. In the Curriculum and Assessment Policy Statement (CAPS) document for home languages (EHL CAPS, 2011, pp. 4-5; SHL CAPS, 2011, pp. 4-5), the Department of Basic Education (DBE) recognises the importance of teaching and learning strategies that develops ‘learners’ higher order reading skills’ in order to produce learners who would use high levels of cognition to solve problems. It was partly this and other DBE scholastic aims that informed the rationale of this study, so as to, among others, establish the feasibility of the aims from teachers’ classroom mediation of visual texts point of view. Thus, data on teacher mediation of visual literacy was collected from audio-recorded lessons of 2 sampled teachers employed at 2 public schools situated in Ekurhuleni region in Gauteng Province. The data was then analysed using the qualitative framework provided in Barrett’s Taxonomy (1968) and Moodley’s (2015) hybrid framework of criteria for analysis of mediation and assessment of visual literacy along with Luke and Freebody (1999) Four Resource Model. The study adopted a constructivist interpretation model to further examine teacher classroom practices. Constructivism is pertinent to this study because the curriculum (EHL CAPS, 2011, pp. 9, 11; SHL CAPS, 2011, pp.10-11) embraces active learning through individual or group participation in the learning process. The findings indicate that the teachers of EHL and SHL use questions to create learning opportunities that enhance visual literacy skills in their home language classroom. However, the teachers’ questioning techniques and classroom activities during visual literacy lessons hinder learner development in critical thinking skills. They do not engender active learning and language development.
A research report submitted to the University of the Witwatersrand, Department of Applied Language Studies, in partial fulfilment of the requirements for the Masters degree
Keywords: Visual Literacy; English Home Language; Sepedi Home Language